Greek gods, heroes, and mythology - Buckey, A. W. (Gods, heroes, and mythology., 2019)
Highlights Greek gods, goddesses, and myths that influenced the belief system of the Ancient Greek culture. Includes text-related questions, resources for further information, a glossary, and color photographs.